AKTUALISASI PENDIDIKAN ISLAM DALAM KELUARGA (Perspektif Al-Qur’an Surat Luqman) - Lukis Alam (Universitas Muhammadiyah Ponorogo, 2016)
Child is a gift from Allah SWT that we must guard. Giving an Islamic education since childhood in the family environment is a mandatory task for both parent. Building an Islamic educational values can be done by telling the story through a letter of the Quran, one of which is the Luqman letter. Islamic education values contained in the Luqman letter are considered capable in forming an Islamic character, especially for children. Telling the story of a letter of Luqman is one choice to guard children as early as possible, from negative environmental influences in this globalization era filled with sophistication and easiness in accessing all forms of information. The concept of Islamic education for children in the family was done by involving aspects of worship, Muslim beliefs and morals as well as children intellectual. Guiding an Islamic Education is the essential foundation for his own survival in the future. It was hoped to increase the sense of belief in Allah SWT.